PENGARUH KEAHLIAN AKUNTANSI KOMITE AUDIT TERHADAP SIFAT-SIFAT PERKIRAAN LABA - Rumaisah Azizah Al Adawiyah; Sudarno Sudarno (Diponegoro Journal of Accounting, 2015)
The aim of this study is to examine the influence of accounting expertise on audit committee on properties  of  earnings forecasts  such  as  accuracy  and  dispersion.  Non-accounting financial expertise, size, surprise, loss, zmijewski score, stdroe, earning level,auispec, audit committee size, audit committee independence, audit committee meet are used as control variable. The population in this study consists of all listed firm in Indonesia Stock Exchange in year 2011 - 2013. Sampling method used is purposive sampling. A criterion for firm which publish its earning forecast. Another criteria is the firm must make and complete data of its audit commitee. Total data of this study is 90 dta.  Then,  there  are  18  samples  that  include  outlier  should  be  excluded  from  samples  of observation. So, the final amounts of the sample are 72 data. Multiple regression used to be analysis technique. The empirical result of this study show that accounting financial expertise on audit commitee has positively significant influenced on accuracy of earning forecasts. Accounting financial  expertise  on  audit  commitee  has  no  significant  influence  on  dispersion  of  earning forecasts.